(0.3+2x)(0.3+2x)=3.266

Simple and best practice solution for (0.3+2x)(0.3+2x)=3.266 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (0.3+2x)(0.3+2x)=3.266 equation:


Simplifying
(0.3 + 2x)(0.3 + 2x) = 3.266

Multiply (0.3 + 2x) * (0.3 + 2x)
(0.3(0.3 + 2x) + 2x * (0.3 + 2x)) = 3.266
((0.3 * 0.3 + 2x * 0.3) + 2x * (0.3 + 2x)) = 3.266
((0.09 + 0.6x) + 2x * (0.3 + 2x)) = 3.266
(0.09 + 0.6x + (0.3 * 2x + 2x * 2x)) = 3.266
(0.09 + 0.6x + (0.6x + 4x2)) = 3.266

Combine like terms: 0.6x + 0.6x = 1.2x
(0.09 + 1.2x + 4x2) = 3.266

Solving
0.09 + 1.2x + 4x2 = 3.266

Solving for variable 'x'.

Reorder the terms:
0.09 + -3.266 + 1.2x + 4x2 = 3.266 + -3.266

Combine like terms: 0.09 + -3.266 = -3.176
-3.176 + 1.2x + 4x2 = 3.266 + -3.266

Combine like terms: 3.266 + -3.266 = 0.000
-3.176 + 1.2x + 4x2 = 0.000

Begin completing the square.  Divide all terms by
4 the coefficient of the squared term: 

Divide each side by '4'.
-0.794 + 0.3x + x2 = 0.000

Move the constant term to the right:

Add '0.794' to each side of the equation.
-0.794 + 0.3x + 0.794 + x2 = 0.000 + 0.794

Reorder the terms:
-0.794 + 0.794 + 0.3x + x2 = 0.000 + 0.794

Combine like terms: -0.794 + 0.794 = 0.000
0.000 + 0.3x + x2 = 0.000 + 0.794
0.3x + x2 = 0.000 + 0.794

Combine like terms: 0.000 + 0.794 = 0.794
0.3x + x2 = 0.794

The x term is 0.3x.  Take half its coefficient (0.15).
Square it (0.0225) and add it to both sides.

Add '0.0225' to each side of the equation.
0.3x + 0.0225 + x2 = 0.794 + 0.0225

Reorder the terms:
0.0225 + 0.3x + x2 = 0.794 + 0.0225

Combine like terms: 0.794 + 0.0225 = 0.8165
0.0225 + 0.3x + x2 = 0.8165

Factor a perfect square on the left side:
(x + 0.15)(x + 0.15) = 0.8165

Calculate the square root of the right side: 0.903603896

Break this problem into two subproblems by setting 
(x + 0.15) equal to 0.903603896 and -0.903603896.

Subproblem 1

x + 0.15 = 0.903603896 Simplifying x + 0.15 = 0.903603896 Reorder the terms: 0.15 + x = 0.903603896 Solving 0.15 + x = 0.903603896 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.15' to each side of the equation. 0.15 + -0.15 + x = 0.903603896 + -0.15 Combine like terms: 0.15 + -0.15 = 0.00 0.00 + x = 0.903603896 + -0.15 x = 0.903603896 + -0.15 Combine like terms: 0.903603896 + -0.15 = 0.753603896 x = 0.753603896 Simplifying x = 0.753603896

Subproblem 2

x + 0.15 = -0.903603896 Simplifying x + 0.15 = -0.903603896 Reorder the terms: 0.15 + x = -0.903603896 Solving 0.15 + x = -0.903603896 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.15' to each side of the equation. 0.15 + -0.15 + x = -0.903603896 + -0.15 Combine like terms: 0.15 + -0.15 = 0.00 0.00 + x = -0.903603896 + -0.15 x = -0.903603896 + -0.15 Combine like terms: -0.903603896 + -0.15 = -1.053603896 x = -1.053603896 Simplifying x = -1.053603896

Solution

The solution to the problem is based on the solutions from the subproblems. x = {0.753603896, -1.053603896}

See similar equations:

| 5x+15/5=35+x | | -6x=7x^2-x-12 | | 7x+28-10=0 | | -11x^2-8x+3=0 | | 6n-75=n | | (0.3+2x)(0.3+2x)=3.27 | | v/6=3 | | 25-10x=7+4x | | 24-5*(3-3x)=-51 | | y-3.25=8.5 | | 5-4*(5+4x)=1 | | 3x^2-7x+11=0 | | P^2-12+9=0 | | x-1/7=6.4 | | 2x+(-10+4x)+13=51 | | m-2.4+2.4=5.3+2.4 | | 12+5*(4-x)=32 | | 2-(9-4x)+10=7 | | c=(5d-2)/(9+7d) | | 3y=81x | | 36x^2-24x=-4 | | 2x+(6+2x)+14=36 | | 15+5*(5+3x)=70 | | 10=-x^2+7x | | 8x-(5x+9)+16=-2 | | 4x+(4x+3)+7=34 | | x-2/3+2/3=6+2/3 | | 3(6-n)=4 | | 2x+5=79-10x | | n-9=27 | | 2y+25=10 | | y-1/4=7/4 |

Equations solver categories